Role Sharing Dalam Aktivitas Domestik (Studi Kasus: Pasangan Usia Muda di Kota Padang) - Yulia Fransisca (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2021)
The purpose of this study is to reveal the forms of role sharing practices for young couples in domestic activities and to identify the obstacles to role sharing practices for young couples in domestic activities in Kubu Dalam Subdistrict, Parak Karakah, Padang, West Sumatera. The author analyzes the structuration theory by Anthony Giddens, with a qualitative approach. The research informants were selected using purposive sampling technique. There are changes that occur in husband and wife couples who work together to resolve these domestic affairs. The form of the division of labor is that the husband cleans the house, does the laundry, looks after and cares for the child. and the obstacles that underlie the absence of Role Sharing are caused by several things. For example, having worked in an area that is far away, working time at the same time as taking care of household matters, busy factors, fatigue after work, and sometimes unstable emotions